1996
DOI: 10.1183/09031936.96.09122468
|View full text |Cite
|
Sign up to set email alerts
|

Role of thromboxane-A2 and cholinergic mechanisms in bronchoconstriction induced by cigarette smoke in guinea-pigs

Abstract: R Ro ol le e o of f t th hr ro om mb bo ox xa an ne e--These results suggest that the bronchoconstriction induced by cigarette smoke is partially mediated by thromboxane A 2 , which is dependent on a cholinergic pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…When anaesthetized guinea-pigs were acutely exposed to less diluted smoke through the tracheostomy tube for 10 min, marked bronchoconstriction occurred within a few minutes [41,42]. When exposing animals to more diluted smoke for only 3 min, it did not cause direct bronchoconstriction, but induced significant airway hyperresponsiveness to inhaled histamine [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When anaesthetized guinea-pigs were acutely exposed to less diluted smoke through the tracheostomy tube for 10 min, marked bronchoconstriction occurred within a few minutes [41,42]. When exposing animals to more diluted smoke for only 3 min, it did not cause direct bronchoconstriction, but induced significant airway hyperresponsiveness to inhaled histamine [7].…”
Section: Discussionmentioning
confidence: 99%
“…This study was started based on previous experience about acute exposure models [7,41,42]. When anaesthetized guinea-pigs were acutely exposed to less diluted smoke through the tracheostomy tube for 10 min, marked bronchoconstriction occurred within a few minutes [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…The most advanced theory is certainly that of bronchialinduced inflammation because of an irritant effect of ETS involving the parasympathic receptors or because of direct damage to the respiratory epithelium resulting in an inflammatory-immune process [27,28]. Some studies in vivo demonstrated, in exposed animals [29] or in human smokers [30], greater concentrations of thromboxane A # or neutrophils, macrophages, pro-inflammatory mediators (interleukin-1β and interleukin-6) and chemoattractants (the monocyte chemoattractant protein-1, MCP-1, and the neutrophil chemoattractant, interleukin-8) in the products of bronchoalveolar lavage. Additionally, the concentrations of macrophages, neutrophils, interleukin-1β and interleukin-8 are elevated in a cigarette dose-dependent manner [30].…”
Section: Discussionmentioning
confidence: 98%
“…Current smoking among males was associated with wheezing. Inhaling cigarette smoke for at least 15 years has been shown to be capable of inducing acute bronchoconstriction in both animals and humans [Hong et al, ; Hong and Lee, ; Matsumoto et al, ; Chiba et al, ]. Moreover, it has been suggested that simultaneous and persistent exposure to airborne allergens and to smoking may have an additional or synergetic effect on the occurrence of adult‐onset asthma [de Nijs et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of GTS episodes reported in the last year was linearly associated with wheezing in both genders. The action of nicotine inhaled through cigarette smoking on bronchoconstriction and increased mucous production have been widely described in the literature, either as direct action on the lungs or on the central nervous system [Hong et al, ; Hong and Lee, ; Matsumoto et al, ; Maouche et al, ]. However, respiratory risks when harvesting tobacco have not been investigated yet.…”
Section: Discussionmentioning
confidence: 99%